PENGAKTIFAN TEMPORARY PROTECTION DIRECTIVE (TPD) DI UNI EROPA UNTUK MENANGANI PENGUNGSI UKRAINA TAHUN 2022 - Rahmadona, Indah; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Russia's invasion of Ukrainian territory in 2022 resulted in infrastructure damage and casualties that forced many of them to flee in search of safety. This caused a new problem for the European Union as an intergovernmental organization that oversees 27 European countries. Because the majority of Ukrainian refugees flee to European Union member countries that border Ukraine. As a result, there was a massive large-scale refugee movement within a short time. The purpose of this paper is to analyze the policies taken by the European Union in dealing with Ukrainian refugees through activation Temporary Protection Directive (TPD) in 2022. This research is qualitative research with data collection sourced from journals, documents and reports from official websites, as well as news articles. The research show that the European Union as an intergovernmental organization helps its member countries to determine policies in dealing problems in the European region, such as the refugee problem. In response to the Ukrainian refugee, European Union member countries agreed to activate the TPD. TPD helps member countries deal with refugees by formulating guidelines to help fulfilling basic matters such as eligible recipients, freedom of movement, residence permits, access to employment, access to social welfare such as housing and medical care, access to education, and family reunification opportunities. Keyword: European Union, Temporary Protection Directive, Ukrainian Refugee.